Produção de membrana composta por poli (álcool vinílico) associada à nerolidol e avaliação de sua capacidade antimicrobiana - Machado, Paola Amanda Paradella (2020)
The analysis of the healing process from the clinical, macroscopic and histological points of view of cutaneous wounds shows that the treatment of cutaneous wounds is dynamic and depends, at each moment, on the evolution of the healing phases, in search of facilitating and accelerating the natural evolution of the wound healing process, the use of substances extracted from plants has been increasing. Therefore, this work intends to produce a polyvinyl alcohol (PVA) membrane obtained by electrospinning, associated with the active principle Nerolidol, a sesquiterpene extracted from plants and evaluate its antimicrobial capacity, to be used as biodegradable dressing in mammalian skin wounds. To obtain the membrane, a polymeric solution of (PVA) was used at a concentration of 8% (w/v), using water as solvent. Subsequently, about 5% ethanol was added, in order to decrease the surface tension of the polymeric solution. In this 5% ethanol, the amount of 25 and 50% (v/m) of nerolidol was added. The electrospinning was performed in the parameters: potential difference of 15kV; distance from the needle to the collector of 12 cm and solution flow of 0.75 mL.h-1. The membranes obtained were characterized using the technique of Scanning Electron Microscopy (SEM), which showed a coalescence of fibers after the incorporation of Nerolidol, being more pronounced for membrane containing 50% of the active principle, with an increase of 61.4% in fiber diameter compared to pure PVA membrane. The contact angle analysis showed that although the membranes are hydrophilic, there was an increase in the contact angle in the presence of Nerolidol, indicating that this substance is mainly found on the surface of the fibers. Furthermore, the Fourier Transform Infrared (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and X-ray techniques indicate that the PVA did not encapsulate the Nerolidol, which probably stayed under the PVA surface. The antimicrobial analyses showed that the most important microorganisms causing infection in skin wounds: Staphylococcus epidermidis, Staphylococcus aureus and Pseudomonas aeruginosa were inhibited against the membrane containing Nerolidol. Therefore, the work is promising in the study of this new biodegradable dressing formed from PVA and Nerolidol with antimicrobial effect on mammalian skin wounds.